From slaves to prisoners of war : the Ottoman Empire, Russia, and international law - Smiley, Will (Oxford : Oxford University Press, 2018)
In this original study, Will Smiley reassesses an aspect of the legacy of the Ottoman-Russian wars in the 18th century: both empires had a long history of slavery, but in the course of the 18th century they worked out a new regional international law that transformed captivity, introducing the concept of prisoners of war.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 20, 2018).
Keywords: Russo-Turkish Wars, 1676-1878.; Prisoners of war -- Turkey -- History -- 18th century; Prisoners of war -- Russia -- History -- 18th century; Turkey -- History -- Ottoman Empire, 1288-1918.; History; Asian history